2017
DOI: 10.12973/eu-jer.6.4.485
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Mathematical Thinking States of Form Teachers on Their Mathematics Teaching Anxieties

Abstract: Abstract:The state of mathematical thinking is considered to have an effect on the formation of anxiety regarding teaching mathematics. It is hypothesized that with the formation of mathematical thinking, the anxiety in teachers regarding teaching mathematics will be reduced. Since mathematical thinking is a skill acquired starting from the early years of education, the anxiety in form teachers in primary school regarding teaching mathematics is important. Within this context, the objective of this study is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
1
4
0
1
Order By: Relevance
“…The mean mathematics teaching anxiety score of the participating teachers was found to be lower than the mean of the scale. The findings obtained in the studies conducted by Bekdemir (2007), Elmas (2010), Hacıömeroğlu ( 2014) Ural (2015), Yorulmaz, Altıntaş, and Sidekli (2017), Deringöl (2018) also support this finding of the current study.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The mean mathematics teaching anxiety score of the participating teachers was found to be lower than the mean of the scale. The findings obtained in the studies conducted by Bekdemir (2007), Elmas (2010), Hacıömeroğlu ( 2014) Ural (2015), Yorulmaz, Altıntaş, and Sidekli (2017), Deringöl (2018) also support this finding of the current study.…”
Section: Resultssupporting
confidence: 89%
“…The mathematical thinking levels of the teachers having graduated from General High Schools and Anatolian High Schools were found to be closer to each other but higher than that of the teachers having graduated from Vocational High Schools. Yorulmaz, Altıntaş, and Sidekli (2017) found that the mean mathematical thinking score of the class teachers is high and this was thought to be because they graduated from the science and mathematics departments of high schools. In other studies conducted on teachers and pre-service teachers, their mean mathematical thinking levels were also found be higher than the mean of the scales used (Ersoy & Güner, 2014;Yorulmaz, Çokçalışkan, & Çelik, 2018;Demirtaş, 2018), which supports the finding of the current study.…”
Section: Resultsmentioning
confidence: 99%
“…Rendahnya hasil belajar matematika diskrit disebabkan kurangnya minat mahasiswa untuk belajar matematika, mahasiswa selalu menganggap matematika sebagai ilmu sukar, dan sulit untuk memahami keabstrakannya, sehingga menimbulkan rasa takut dan tidak adanya minat mahasiswa dalam belajar matematika. (Sapta, 2018;Yorulmaz, Altintas, & Sidekli, 2017) menyatakan bahwa proses pembelajaran dapat diikuti dengan baik dan menarik perhatian siswa ketika menggunakan metode pembelajaran yang sesuai dengan tingkat perkembangan siswa dan sesuai dengan materi pembelajaran. juga menuntut siswa untuk mampu berpikir logis, kritis, analisis, kreatif, dan mampu menciptakan kerjasama yang baik.…”
Section: Pendahuluanunclassified
“…As it is seen in the literature, many studies have been conducted in this field starting from the importance of reflections of mathematics teaching anxiety on the mathematics teaching process. In this context, studies were conducted about teachers/pre-service teachers'; mathematics teaching anxiety and mathematics anxiety (Brown, Westenskow & Moyer-Packenham, 2011;Gresham, 2010), learning/teaching styles (Stevens, 2010), genders (Peker & Halat, 2008) , mathematics/mathematics teaching self-efficacy perceptions (Ural, 2015), mathematics teaching/learning beliefs (Peker & Ulu, 2018), mathematical values (Yazıcı, Peker, Ertekin & Dilmaç, 2011), learning environment (McMinn, 2019), micro-teaching (Fadlelmula, 2013), teaching experiences (Brown, Westenskow & Moyer-Packenham, 2011), mathematical thinking (Yorulmaz, Altıntaş & Sidekli, 2017), metacognitive awareness (Öztürk & Serin, 2020) and technology usage (Zengin, 2017). Additionally, scale development (Liu, 2016;Peker, 2006;Sarı, 2014) and adaptation studies (Aytekin, Türkmenoğlu, & Arıkan, 2017;Hunt & Sarı, 2019) for mathematics teaching anxiety are among the studies conducted.…”
Section: Introductionmentioning
confidence: 99%